Penerapan Urban Farming dengan Sistem Hidroponik Menggunakan Botol Bekas melalui Kuliah Kerja Nyata Mahasiswa (KKNM) Virtual - Lukito; Ahmad Thoriq; Rizky Mulya Sampurno (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Hydroponically planting vegetables is something new for most of the KKNM participants. KKNM activities are carried out for 30 working days based on modules and WhatsApp Group. The vegetable cultivation module with a hydroponic system using used bottles is systematically arranged, equipped with pictures to make it easy for each KKNM participant to implement. WhatsApp Group is used as a means of discussion and consultation. This virtual KKNM activity aims to produce vegetables through a hydroponic system from used bottles and distribute harvested vegetables to the community. The implementation of the activity begins with the preparation of tools and materials, sowing seeds, preparing planting media, maintaining plants, until harvesting. Finally, the distribution of crops to the closest neighbors. The results showed that used plastic bottles can be used as a hydroponic planting medium with the axis system. Transplanting the seedlings to the used wick bottle media that has been filled with nutrients was carried out on the 12th day. Plant maintenance is carried out by periodically controlling the nutritional condition. Harvesting and distribution of vegetables was carried out on the 25th day after transplanting. This Virtual KKNM activity is proven to be able to increase participants' knowledge and skills, and to inspire people to do the same.